2009
DOI: 10.1111/j.1467-999x.2009.04069.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consumption and Production Structure on Growth and Distribution. A Micro to Macro Model

Abstract: The paper offers a theoretical analysis of long-run economic growth as an outcome of structural changes. We model the microeconomic behaviour of firms in the final good and capital sectors, and the evolution of classes of workers/consumers. We carefully craft economic behaviour onto empirical evidence, and solve the model numerically. The results illustrate the microeconomic properties of the simulated growth patterns. In particular, we observe and explain the interactions between technological change, firm or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 69 publications
0
72
0
4
Order By: Relevance
“…3 Here, we briefly discuss the main structure and dynamics of the model. In the following sections we highlight the aspects of the model that differ from Ciarli et al (2010), and on which the investigation in this paper depends.…”
Section: The Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Here, we briefly discuss the main structure and dynamics of the model. In the following sections we highlight the aspects of the model that differ from Ciarli et al (2010), and on which the investigation in this paper depends.…”
Section: The Modelmentioning
confidence: 99%
“…The model is an extension of the model described in Ciarli et al (2010) and Ciarli et al (2012), where a detailed description can be found. 3 Here, we briefly discuss the main structure and dynamics of the model.…”
Section: The Modelmentioning
confidence: 99%
See 3 more Smart Citations